DESIGN OF TAPERED WIND TURBINE USING VARIOUS NACA 24112 AIRFOILS IN SEMAYAN VILLAGE CENTRAL LOMBOK REGENCY - Tira, Hendry Sakke; Zulfikar, Muhammad Ponco (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2024)
This research focuses on designing and optimizing a tapered wind turbine employing NACA 24112 airfoils, specifically tailored for Semayan Village in Central Lombok West Nusa Tenggara province. Given the escalating global energy demand and the depletion of fossil fuels, the study aims to explore alternative energy solutions. The chosen horizontal axis turbine, equipped with an increased number of blades, seeks to maximize the power coefficient and overall efficiency. The NACA airfoil model, coupled with Q-Blade v0.963 software, was employed for simulations after conducting wind speed measurements in Semayan Village. The collected data indicated moderate wind speeds, aligning with the selection of the Taper blade design. The blade design process involved comprehensive system efficiency calculations and twist angle optimizations to enhance overall turbine performance and extend its lifespan. Rotor simulations revealed a noteworthy peak in the power coefficient (Cp), reaching 45% at Tip Speed Ratio (TSR) 7, indicating an optimal point for power generation. However, the study emphasizes the importance of selecting an appropriate TSR, as efficiency diminishes at higher TSR values. This research highlights the potential of wind energy as a viable and sustainable solution, particularly for regions with limited access to electricity. It advocates for the broader adoption of renewable energy sources to address the evolving energy landscape.